ANALISIS MINAT DAN KEMAMPUAN DASAR AKUNTANSI TERHADAP TINGKAT PEMAHAMAN MAHASISWA PENDIDIKAN INFORMATIKA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2018)
This study aims to analyze the influence of students' basic interests and accounting skills on the level of understanding of students of informatics education STKIP PGRI West Sumatra on computer accounting courses. To be able to take courses in computer accounting there are prerequisite courses that must be taken by students, namely introductory accounting 1 and introductory accounting 2. This is because these two courses are the main knowledge base of students to be able to master accounting computer material easily. The results of the study explain that there is a positive and significant influence between interests on the level of student understanding in computer accounting courses, accounting skills have a positive and significant influence on students' level of understanding in computer accounting courses. The article clearly discusses the influence of basic accounting interests and abilities on the level of understanding of students in computer accounting courses, especially students of informatics education STKIP PGRI West Sumatra.